Architecture is still useful? Is there any relationship with teaching? - Padilla, José Vicente (Estoa. Journal of the Faculty of Architecture and Urbanism, 2018)
The current situation of the teaching architecture turns out to be worrying in the face of a changing and complex society. The career is sacrificed, frustrating, demanding and expensive. It requires a great motivation to face it, but… for what? Does the present society offer the opportunities in order that so much effort will be compensated ? It is not only about the economic sense, but mainly about the personal accomplishment of the architect, in the fulfillment of real objectives regarding the development of the activities that the legal framework allows us. Some colleagues share this concern and have done work on it. We make a brief analysis of the opinions of some of them and we relate them to the Ecuadorian context of the 21st century, specifically in the case of the Central University, Faculty of Architecture, in Quito. This paper is supported in a descriptive research, aimed to the protagonists of the architecture and teaching, a population that wants to reflect a coherent universe for the subject, and which consists of the processing of surveys and focus groups, developed from an initial theoretical reflection, answering specific questions. In the development of the article, we will try to summarize the most important of these references, and the results of the research carried out, to expose later some personal reflections that try to contribute to find solutions from the approach of teaching Architecture.